Insomnia and Telomere Length in Older Adults - Carroll, Judith E; Esquivel, Stephanie; Goldberg, Alyssa; Seeman, Teresa E; Effros, Rita B; Dock, Jeffrey; Olmstead, Richard; Breen, Elizabeth C; Irwin, Michael R (Sleep (New York, N.Y.), 2016)
Insomnia, particularly in later life, may raise the risk for chronic diseases of aging and mortality through its effect on cellular aging. The current study examines the effects of insomnia on telomere length, a measure of cellular aging, and tests whether insomnia interacts with chronological age to increase cellular aging. A total of 126 males and females (60-88 y) were assessed for insomnia using the Diagnostic and Statistical Manual IV criterion for primary insomnia and the International Classification of Sleep Disorders, Second Edition for general insomnia (45 insomnia cases; 81 controls). Telomere length in peripheral blood mononuclear cells (PBMC) was determined using real-time quantitative polymerase chain reaction (qPCR) methodology. In the analysis of covariance model adjusting for body mass index and sex, age (60-69 y versus 70-88 y) and insomnia diagnosis interacted to predict shorter PBMC telomere length (P = 0.04). In the oldest age group (70-88 y), PBMC telomere length was significantly shorter in those with insomnia, mean (standard deviation) M(SD) = 0.59(0.2) compared to controls with no insomnia M(SD) = 0.78(0.4), P = 0.04. In the adults aged 60-69 y, PBMC telomere length was not different between insomnia cases and controls, P = 0.44. Insomnia is associated with shorter PBMC telomere length in adults aged 70-88 y, but not in those younger than 70 y, suggesting that clinically severe sleep disturbances may increase cellular aging, especially in the later years of life. These findings highlight insomnia as a vulnerability factor in later life, with implications for risk for diseases of aging.